Emerging nations personality evaluation scale - Allen, Edmund E.; Rich, Thomas A.; Wright, Peter C.; Fleming, Paul (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Personality evaluations of illiterate Latin American peasants, particularly when data are obtained by educated, urban interviewers, often elicit “yes/no,’’ “ don’t know,” or invalid guesses or attempts- to-please responses.